Home Features and Assistive Technology for the Home-Bound Elderly in a Thai Suburban Community by Applying the International Classification of Functioning, Disability, and Health - Supawadee Putthinoi (2018)
© 2017 Supawadee Putthinoi et al. The ageing population is having an impact worldwide and has created a serious challenge in Thailand's healthcare systems, whereby healthcare practitioners play a major role in promoting independent interaction of their client's abilities, as well as environmental factors. The purpose of this study was to survey features of the home and assistive technology (AT) for the home-bound elderly in the community of Chiang Mai, Thailand. Home evaluation included features inside and outside the home, and AT was based on the International Classification of Functioning, Disability, and Health (ICF) concept. Methods included observation and an interview that were used by the researcher for evaluation. The study found that every home had at least one hazardous home feature such as inappropriate width of the door, high door threshold, tall stair steps, no bedside rail, and inappropriate height of the toilet pan. AT was found in houses as general products and technology for personal use in daily living and for personal indoor and outdoor mobility as well as transportation. Therefore, home features and AT can afford the home-bound elderly independent living within the community. Perspective AT according to the ICF concept could provide a common language for ageing in place benefits.